1990
DOI: 10.1093/carcin/11.10.1727
|View full text |Cite
|
Sign up to set email alerts
|

The levels of quinone reductases, superoxide dismutase and glutathione-related enzymatic activities in diethylstilbestrol-induced carcinogenesis in the kidney of male Syrian golden hamsters

Abstract: The level of quinone oxidoreductases (microsomal and cytosolic DT-diaphorase, NADPH-cytochrome P450 reductase and NADH-cytochrome b5 reductase), superoxide dismutase and glutathione-related enzymatic activities in diethylstilbestrol (DES)-induced carcinogenesis in kidney from Syrian golden hamsters are presented. Animals that exhibited two different stages of DES-induced carcinogenesis in kidney--pre- and neoplastic lesions and tumorous lesions (after 6 and 8 months of continuous exposure to DES respectively)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Methods reported in the literature do not appear to have been validated, i.e. the non-dicoumarol-inhibitable reduction of cytochrome c (Segura-Aguilar et al, 1990) or the NADHdependent reduction of cytochrome c (Plumb et al, 1994), and assume that cytochrome b5 reductase is the only enzyme responsible for the NADH-dependent reduction of cytochrome c. Our data indicate that this assumption is not valid. From Figure 4 it is evident that cytochrome b5 reductase activity does not account for all of the NADH-dependent reduction of cytochrome c in any cell line, as assessed using pHMB as a selective inhibitor.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Methods reported in the literature do not appear to have been validated, i.e. the non-dicoumarol-inhibitable reduction of cytochrome c (Segura-Aguilar et al, 1990) or the NADHdependent reduction of cytochrome c (Plumb et al, 1994), and assume that cytochrome b5 reductase is the only enzyme responsible for the NADH-dependent reduction of cytochrome c. Our data indicate that this assumption is not valid. From Figure 4 it is evident that cytochrome b5 reductase activity does not account for all of the NADH-dependent reduction of cytochrome c in any cell line, as assessed using pHMB as a selective inhibitor.…”
Section: Discussionmentioning
confidence: 71%
“…The method of Segura-Aguilar et al (1990) also assumes that dicoumarol is a selective inhibitor of DT-diaphorase. We found that dicoumarol did not inhibit the NADH-dependent reduction of cytochrome c catalysed by mouse liver microsomes (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas SOD, catalase and GPX respond to a number of pro-oxidant conditions, including changing oxygen tension, induction of DT-diaphorase is mainly related to exposure to xenobiotics. Increases in mRNA, protein and/or catalytic activity of the former enzymes have been demonstrated in bacteria following exposure to the redox cycling xenobiotics menadione and paraquat (SOD) and H202 (catalase) (Storz et al 1990 (SOD and catalase: Videla et al 1990), and carcinogenesis (variously, SOD, catalase and/or GPX: Vo et al 1988, Segura-Aguilar et al 1990, Reiners et al 1991. Mammalian DT-diaphorase is part of the gene battery that includes cytochrome P4501A1 and is induced both by xenobiotics that bind to the Ah receptor and certain pro-oxidant xenobiotics that affect gene regulation via other mechanisms (Nebert et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The hydroxy radicals thus formed modify the DNA bases into thymine glycol, 8-OH-dG and others. One example of oxygen radical mediated carcinogenesis is presented in figure 2 (Segura-Aguilar et al 1990). Diethylstilboestrol (DES), a renal carcinogen, is enzymically reduced by NADPH-cytochrome P-450 reductase , and an equilibrium between quinone and semiquinone gives rise to reactive oxygen radicals such as Superoxide anion and hydroxy radical.…”
Section: Tumour Initiationmentioning
confidence: 99%